(untitled) (International journal of artificial intelligence, 2024)
This article discusses the art of music, its historical development, the restoration of our national musical heritage and its harmony with national values ​​in the spiritual life of our people. It also describes the study, mastery, and promotion of classical musical traditions, the role of our national musical culture in shaping the spiritual worldview of the younger generation.